Historic income versus inflation-adjusted income in the dividend decision - D. P. Du Plessis; A. A. Archer; J. F. Affleck-Graves (South African Journal of Business Management, 1986)
An attempt is made to determine to what extent companies take into account the effects of inflation in formulating their dividend decisions. The research design incorporates a two-stage regression approach which permits a determination of the incremental explanatory power of collinear variables. The research findings suggest that dividend decisions are best explained in terms of historic earnings. It therefore appears as if management does not take the effects of inflation into account in formulating dividend policy. This could have serious implications for the survival of a company because it could result in a real dividend cover of less than one.
Keywords: 650